A study on evaluating the effectiveness of pre- and posttest model of learning microbiology in a tertiary peripheral medical college of West Bengal - Indrajit Gupta; Simit Kumar; Abhilekha Bishwas; Arani Debnandi (Wolters Kluwer Medknow Publications, 2024)
Background and Aims: Traditional didactic lecture methods were previously dominant in medical education in India, where students tend to lose their concentration after 15-20 min of lectures. In the context of competency-based medical education, a teaching-learning method that includes pre- and posttests were hypothesized to have the potential to enhance the learning process and make difficult topics easier for students to understand. This method was implemented for phase 2 MBBS students at Rampurhat Government Medical College and Hospital in India. Materials and Methods: The study was conducted in the department of microbiology in October 2021, with 65 male and 33 female students who provided informed consent. All the students were allotted immunology topics and were asked to present seminars. The students were required to complete a pretest and posttest questionnaire covering key areas of immunology. The mean and standard deviation of the scores were calculated. Paired Student's t-test was used to compare pre- and posttest scores, and P values were calculated using SPSS 20. A P < 0.05 was considered statistically significant. Results: The total number of correct responses on the posttest was significantly higher (P < 0.05) than the number of responses on the pretest. Gender-specific posttest responses were also significant (for males, P < 0.001; for females, P < 0.001). Overall marks were improved on the posttest, and the mean scores among all the students showed significant improvement in their posttest scores compared to their pretest scores. Conclusions: Evaluating students using a pretest and posttest was found to be a practical and feasible tool for learning. The majority of students reported that this method of learning helped them engage in critical thinking and understand topics more systematically, which they believed would contribute to their success as competent Indian Medical Graduates.